Tacitness, Learning, and International Expansion: A Study of Foreign Direct Investment in a Knowledge-Intensive Industry - Martin, Xavier; Salomon, Robert (Organization Science, 2003)
This paper examines the impact of knowledge tacitness on a firm's propensity to establish plants in foreign rather than domestic locations. Our predictions build on knowledge-based, internalization, and evolutionary theories of foreign direct investment. We argue that the tacitness of technology has an inverted-U effect on the propensity to undertake foreign investment. We also expect that as a firm learns about a technology, it will become more likely to make foreign investments. We examine two forms of learning: that which accumulates as a function of the number of plants previously built by the firm (transfer-based learning), and that which accumulates as a function of time since the firm started using a technology (time-based learning). We investigate empirical effects in a sample of investments in the memory segment of the semiconductor industry. Our predictions about the curvilinear effect of tacitness are supported. The results also suggest that learning is a matter of taking time to become acquainted with the use of the technology, and of gaining experience through successive foreign plant investments. The study adds to the understanding of the effects of knowledge on corporate expansion.